A11 THE INFLAMMATORY CASPASES COORDINATE MUCOSAL RESTRICTION OF SALMONELLA THROUGH THE EPITHELIAL-INTRINSIC INFLAMMASOME. (15th March 2019) - Crowley, S M; Allaire, J M; Han, X; Graef, F A; Stahl, M; Knodler, L; Rauch, I; Vallance, B
Abstract: Background: Intestinal epithelial cells (IECs) are located at the interface between the gut lumen and the underlying mucosal defense system. Here, they play a central role in the coordination of intestinal homeostasis, tempering pro-inflammatory responses but remaining rapidly responsive to noxious stimuli such as an enteric pathogen. One mechanism by which IECs engage in innate immune defense is through the activation of the inflammasome which mobilizes the inflammatory caspases; Caspase-1 and -11. Aims: Here, we investigate the role of the inflammasome in IEC and overall mucosal defense against the enteric pathogen Salmonella enterica serovar Typhimurium SL1344. Methods: Streptomycin-pretreated wildtype C57BL/6, Casp1/11 deficient (−/−), Casp1−/− and Casp11−/− mice were orally infected and S. Typhimurium burdens determined in intestinal tissues at 18h post infection. Results: Increased cecal and luminal pathogen loads were observed for all caspase-deficient mice compared to wild type, which correlated with increased IEC intracellular S. Typhimurium burdens. Interestingly, despite increased bacterial loads, cecal pathology scores for all deficient mice were decreased, especially with regard to 'IEC damage' and 'goblet cell loss'. To determine if the increased burdens were due to the loss of IEC-intrinsic inflammasomes, enteroid monolayers were derived and infected. This revealed significantly increased intracellular burdens in caspase deficient monolayers as compared to wild type, in concert with a marked decrease in IEC sloughing. Peak inflammatory caspase activity was displayed in sloughing wildtype IECs, suggesting IEC-intrinsic inflammasome restricts S. Typhimurium infection through infected IEC expulsion. To examine the role of inflammasome signaling on mucosal defense, mucin layer thicknesses were evaluated by Muc2 immunostaining. After infection, wild type tissue demonstrated a dramatic increase in mucus thickness while caspase deficient mice displayed only a marginal increase. Similarly, expression of the antimicrobial lectins Reg3γ and β was dramatically increased in infected wildtype mice compared to caspase deficient mice. Since mucin release and Reg3 induction have been previously linked to the cytokine IL-22, and IL-22 expression was increased in infected wildtype mice, we tested the effects of neutralizing IL-22. This revealed increased S. Typhimurium burdens and decreased infection-induced mucin secretion, while no differences were observed in Casp1/11−/− treated with either neutralizing antibody or isotype control. Conclusions: These results thus indicate that the intestinal epithelium utilizes inflammasome signaling to coordinate multiple layers of innate defense at the gut mucosal surface to ultimately restrict enteric pathogen infections and systemic spread. Funding Agencies: CCC, CIHRNIH